The Relation between(Number of cigarettes and duration)with 2nd polycythemia in Baghdad (Journal of the College of Basic Education, 2022)
The study includes effect of smoking and relation between the number of cigarettes smoking and duration on 2nd polycythemia.And the main causes of increasing the Hb and PCV result on the smokersBy measured the Hb & PCV for 30 patients those have a 2nd polycythemia due to heavy long duration of cigarettes smoking.These reading show there are relation between the No. of cigarettes and duration on the increase Hb & PCV result .